Fluid-enhanced tunable diffraction with an elastomeric grating - Pada, Caironesa T (Archīum Ateneo, 2017)
We replicate a diffraction grating by soft lithography. Tunable diffraction is accomplished by modifying groove spacing through the application of strain on the elastomeric replica. The range of strain-variable diffraction angles is extended by adding a refracting liquid layer to the grating. Using a water layer, the diffraction angle is tuned from 38 to 33.4 deg with an applied strain of 17.7%. With an equal amount of strain, employing a glycerol layer results in the diffraction angle varying from 38.8 to 34.4 deg. Our experimental results are accurately described by the combined effects of diffraction by a deformable grating and refraction by a fluid with a curved surface.